Ibnu Qayyim Al-Jauziyyah's Ways to Verification of Considered Cause | طرق تعليل الأحكام عند الإمام ابن قيم الجوزية - Zuhrotul Ain Mansur (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2009)
Verification of considered cause ( ta'lil al-ahkiim) together with the objectives of Shariah (maqiisid al-Shari'ah) is among the most important issues discussed by the experts of Jurisprudence. This article analyses the procedures of establishing causes for a certain law according to Ibnu Qayyim Al-Jauziyah, a prominent salafi scholar who has written the subject in his book